Comparison of managers and employees’s views about the effects of clinical governance on patient safety - Rostami, mitra; Zaghari Tafreshi, mansooreh; Atashzadeh-Shoorideh, foroozan; Alavi Majd, hamid (Advances in Nursing & Midwifery, 2015)
Background& aim: Ensuring the patient safety is the first step for quality improvement in health care systems. Clinical governance model , with a systemic approach, a framework for quality assurance. Implementation of clinical governance requires managers and staff contribution. The aim of this study was to compare the manager’s and employees’s views about the effect of clinical governance on patient safety in hospitals of Alborz university of medical sciences . Materials and Methods: A descriptive - comparative ,design was used. The sample of the study consisted of 129 managers and 251 employees. The entire population of managers were included in the study. The employees were included in the study by using quota sampling method. Data were collected by a questionnaire. The questionnaire consisted of demographic information and questions regarding the seven components of clinical governance. The validity of the questionnaire was assured by computing CVI (0.85). The reliability of the questionnaire was assessed by internal consistency (α=0.98) and test re test .Data were analyzed by SPSS 16 software. Results: Almost all managers ( 96.9%) and majority of employees (92.4%) strongly agreed with the significant impact of clinical governance on patient safety. There was no significant difference between managers’ and employees’ views Conclusion: The managers and employees had a positive view on clinical governance and its effect on patient safety. This finding shows that there is a willingness and readiness for implementation of clinical governance in hospitals of Alborz university of medical sciences. Keywords: Clinical governance, Patient, Perspective, Hospital